IDENTIFIKASI SPORA CENDAWAN MIKORIZA ARBUSKULAR (CMA) PADA BERBAGAI RHIZOSFIR PISANG DI LAHAN ENDEMIK - Eti Farda Husin; Eri Sulyanti; Adrinal Adrinal; Yefriwati Yefriwati (Jurnal Solum, 2008)
Banana is one of fruit commodity having been widely cultivated by people and has high potency for agribusiness.  However, there are some constraints for the cultivation, such as soil fertility and disease attack.  Nowadays, tne main disease causing low banana production in West Sumatra is wilt due to Fusarium.  One way being developed to improve banana production in endemic land is by using bioagent.  This research was aimed to identify spores of mycorrizhae in several endemic land.  The result showed that there were various types of MVA found in tested locations (Agam, Solok, and Padang Pariaman regencies).  Glomus was one genus that was always found in each location.  Therefore, the glomus sp was quite potential to explore and and proliferation as a good innoculant to improve growth of banana plant.  The highest amount of MVA sport found in Padang Pariaman regency (especially in Pasar Usang area) was 195/20 g soil (Glomus), then followed by Acaulospora (121 spora/20 g soil) and Gigaspora (65 spora/20 g soil).Key Words: Banana, Fusarium, Wilt, Bioagent, MVA